1986
DOI: 10.1210/endo-118-6-2594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estradiol and Progesterone on Calcitonin Secretion*

Abstract: Estrogen therapy has been used to inhibit bone resorption and prevent osteoporosis in postmenopausal women. Previous studies have disagreed as to whether the mechanism of estrogen action involves stimulation of calcitonin (CT) secretion. We evaluated the direct effects of 17 beta-estradiol (E2) and progesterone (Prog) on CT secretion from the thyroid C cells of 8-day-old rats in vitro. Both E2 and Prog caused a significant stimulation of CT secretion within 1 h, which was progressive for the 3-h observation pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 17 publications
3
24
0
2
Order By: Relevance
“…The action of estradiol to increase the expression of the PTH and calcitonin genes, and the presence ofthe estrogen receptor mRNA and protein in the parathyroid and C cells, as shown in this study, together with the earlier reports of a direct effect of estrogens to increase PTH and calcitonin secretion (16)(17)(18)(19) establish that these two organs are target organs for estrogens.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The action of estradiol to increase the expression of the PTH and calcitonin genes, and the presence ofthe estrogen receptor mRNA and protein in the parathyroid and C cells, as shown in this study, together with the earlier reports of a direct effect of estrogens to increase PTH and calcitonin secretion (16)(17)(18)(19) establish that these two organs are target organs for estrogens.…”
Section: Discussionsupporting
confidence: 85%
“…Our results, together with the earlier in vitro reports of a direct effect of estrogens on PTH and calcitonin secretion (16)(17)(18)(19), indicate that the effect of estrogens to increase PTH and calcitonin levels is a direct effect ofestrogens on the parathyroid and C cells, respectively. In addition we have preliminary data with bovine parathyroid cells in primary culture, and a calcitonin producing cell line, that estrogens in vitro increase PTH and calcitonin mRNA levels, respectively (Naveh-Many, T., and J.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The dose of 17(3-estradiol used in the present in vitro studies (100 nmol/I) was shown to achieve a maximal increase of CT secretion by thyroparathyroid gland complexes of 8-d-old rat pups (Greenberg et al, 1986) (Naveh-Many et al, 1992), and also with the fact that estradiol given to ovariectomized animals prevents the decrease in CT mRNA levels (Naveh-Many et al, 1992;Lamari et al, 1994 (Russo et al, 1988;Collignon et al, 1992) and enhances the biosynthesis and release of both CT and CGRP (Lamari et al, 1994) in CA-77 C cells has already been reported. All-trans-retinoic acid also was shown to decrease both CT and CGRP mRNAs in CA-77 C cells and the secretion of both peptides (Lamari et al, 1994).…”
Section: Discussionmentioning
confidence: 78%
“…In oophorectomized rats, the plasma CT response to a calcium challenge is impaired and can be restored to normal levels by estrogen replacement therapy (Catherwood et al, 1983). Rat pup thyroid incubation studies demonstrate that estradiol can stimulate CT secretion in vitro (Greenberg et al, 1986). In contrast, in the human C cell carcinoma cell line (TT) with well-documented estrogen receptors, estradiol induces a dose-dependent inhibition of CT secretion (Lazaretti-Castro et al, 1991).…”
Section: Introductionmentioning
confidence: 99%